Neurogenic Pulmonary Edema (A Case Report) - Funda Gümüş; Salih Mehmet Sevdi; Kerem Erkalp; Güneş Özlem Ülger; Gökhan Bostan; Ayşin Alagöl (Galenos Yayinevi, 2012)
Neurogenic pulmonary edema is a life threatening complication of severe central nervous system injury. The most common cause of neurogenic pulmonary edema is subarachnoid hemorrhage followed by head trauma and epilepsy. The rare causes are cervical spine trauma, multiplesclerosis, cerebellar hemorrhage and intracranial tumors. Neurogenic pulmonary edema is characterized by an increase in extravascular lung water in patients who have sustained a sudden change in neurologic condition. The exact pathophysiology is unclear but it probably involves an adrenergic response to the central nervous system injury which leads to increased catecholamine, pulmonary hydrostatic pressure and increased lung capillary permeability. The presenting symptoms are nonspecific and often include dyspnea, tachypnea, tachycardia, hypoxemia, pinkfroty secretion, bilateral pulmonary infiltrates and crackles. These symptoms start within minutes or hours and resolves 48-72 hours that typically for neurogenic pulmonary edema. Basic principles of treatment, surgical decompression, reduce intracranial pressure, controlled ventilation with suplemental oxygen, positive end expiratory pressure and diuresis. We report a case with neurogenic pulmonary edema that occured after head trauma. (Journal of the Turkish Society Intensive Care 2012; 10: 59-62)